Peramalan Pemakain Listrik Menggunakan Metode Double Exponential Smoothing Pada PLN. ULP Jatiwangi - Virgiyanti; Musfiroh (STIKOM POLTEK CIREBON, 2023)
Population growth and rapid economic growth have led to higher demand for electrical energy, so it is necessary to provide and distribute adequate electricity. The State Electricity Company is an institution that distributes electricity in various parts of Indonesia. Provision of electricity supply can occur obstacles that hinder community activities. The reasons are a lack of supply, maintenance constraints, and extreme weather disturbances. The unbalanced capacity of electricity supply and demand for electrical energy can cause problems for consumers. Therefore, it is necessary to forecast electricity consumption for the next one year to be able to balance consumer demand with electricity supply capacity. The Double Exponential Smoothing method is used in this study. The results are for one period carried out from each category. Social customer category was 338180.07 kwh, household was 11720101.36 kwh, business was 1252099.755 kwh, industry was 7890454.24 kwh, government was 102954.03 kwh with a MAPE value of 4.55%, household category with MAPE of 4.83%, business category with MAPE of 111.52%, industry category with MAPE of 8.32%, and government category with MAPE of 7.95%.